Flood Notification System - Shbier, Mohammed Z. D. (2006)
Floods occur in many countries every year and often cause great losses. How to monitor and notify flood management teams and people is the key problem for flood pre-disaster management. In Malaysia, flood disaster situation is still managed manually through multi-organization team according to standard operation procedure for disaster management. In current situation there is a delay in notifying those organizations that the situation is dangerous. The communication between those organizations is done manually, which generates a certain amount of risk in case of human error and of course its risky consequences. This study has developed a flood notification system that acts as a communication tool between disaster management organizations. The notification could be done through SMS and email.